2019
DOI: 10.3389/fimmu.2019.01450
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme A Stimulates pDCs to Promote Adaptive Immunity via Induction of Type I IFN

Abstract: Granzyme A (GzmA), together with perforin, are well-known for their cytotoxic activity against tumor or virus-infected cells. In addition to this cytotoxic function, GzmA stimulates several immune cell types and induces inflammation in the absence of perforin, however, its effect on the dendritic cell (DC) is unknown. In the current study, we showed that recombinant GzmA induced the phenotypic maturation of plasmacytoid DCs (pDCs) and conventional DCs (cDCs), but not their apoptosis. Particularly, GzmA made pD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…Additionally, intestinal GrA + Th cells in aGVHD mice did not express perforin (data not shown). GrA has other reported roles in promoting inflammatory cytokine and chemokine production (IL-1β, IL-6, TNF, MCP-1) via interaction with TLRs (42)(43)(44)(45). However, these cytokines were not differentially expressed within the intestines, and only MCP-1 was significantly reduced in the serum of Gzma -/recipient mice.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, intestinal GrA + Th cells in aGVHD mice did not express perforin (data not shown). GrA has other reported roles in promoting inflammatory cytokine and chemokine production (IL-1β, IL-6, TNF, MCP-1) via interaction with TLRs (42)(43)(44)(45). However, these cytokines were not differentially expressed within the intestines, and only MCP-1 was significantly reduced in the serum of Gzma -/recipient mice.…”
Section: Discussionmentioning
confidence: 94%
“…GZMA is one of the key genes to quantify the cytolytic activity (CYT) of tumor cells 31 , the CYT factor was widely used to measure the activation of immunocytes for the RNA sequence data 32 , 33 . Shimizu et al 34 reported that GZMA could activate the plasmacytoid dendritic cells and eliciting antigen-specific cytotoxic CD8+ T lymphocytes (CTLs). Rchiad et al 35 reported the GZMA has a tumor suppressor function in T. annulata-infected bovine host leukocytes and in human B-lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…These genes, which signi cantly varied within the three phenotypes, possibly contributed to form the heterogenous TIME of HCC. In addition, many genes have been reported to be critical in immune response, such as CD27, CD8A, GZMA and IL7R [46][47][48][49]. The GO and KEGG annotation also displayed intensive immune phenotypes ( Figure S6A-S6B, Table S10-S11).…”
Section: Methylation Modi Cation and Regulation Of The Time Phenotypesmentioning
confidence: 96%